Fermented Dendrobium officinale polysaccharides protect UVA‐induced photoaging of human skin fibroblasts. Issue 4 (7th February 2022) - Zhang, Yongtao; You, Shiquan; Wang, Dongdong; Zhao, Dan; Zhang, Jiachan; An, Quan; Li, Meng; Wang, Changtao
Abstract: In this study, Fourier transform infrared spectroscopy (FT‐IR), gel permeation chromatograph‐liquid chromatography (GPC‐LC), and scanning electron microscopy ( SEM ) were used to analyze the molecular characteristics of fermented Dendrobium officinale polysaccharides (FDOP) by Lactobacillus delbrueckii bulgaricus . The characteristic structural peak of FDOP was more prominent, showing a smaller molecular structure, and its porous structure showed better water solubility. The protective effect of FDOP on the damage of human skin fibroblasts (HSF) caused by ultraviolet (UV) radiation was investigated by evaluating its antioxidative and antiaging indices. The results showed that the antioxidant capacity of HSF was improved, and the breakdown of collagen, elastin, and hyaluronic acid was reduced, thus providing effective protection to the skin tissue. The antioxidative property of FDOP was explored using Nf‐E2‐related factor 2‐small interfering RNA‐3 (Nrf2‐siRNA‐3) (Nrf2‐si3) and qRT‐PCR (quantitative reverse transcription polymerase chain reaction), and the antiaging property of FDOP was explored using Western Blot and qRT‐PCR. The results show that FDOP can up‐regulate signal transduction of the Nrf2/Keap1 (Kelch‐like ECH‐associated protein 1) and transforming growth factor‐β (TGF‐β)/Smads pathways to reduce antioxidative damage and antiaging effects. Therefore, this study provides a theoretical basis for FDOP as a novel functional agent that can be used in the cosmetic industry. Abstract : The regulation of human skin fibroblast (HSF) protection mechanism explored by fermented Dendrobium officinale polysaccharides (FDOP) in this experiment is roughly shown in Figure 7. It is through stimulating the conduction of Nf‐E2‐related factor 2/Kelch‐like ECH‐associated protein 1 (Nrf2/Keap1) and transforming growth factor‐β (TGF‐β)/Smads signaling pathways to upregulate the expression of downstream target genes.